Freud: A life of our time - Peter Gay (W. W. Norton, 1988)
The book presents the world of Sigmund Freud: his family, his city, his professional strugges, his long, extraordinarily friutful and embattled life. It sees him at work in times of declining liberalism, devastating war, uneasy peace, the rise of Hitler and the fall of Austria. The book probes Freud's mind, uncovers Freud's passions, and follows Freud's astonishing career. It analyses Frued the psychoanalyst as politician, seeking support for his controversial findings